The consequence of station blackout in a nuclear power plant - Olifant, Tshepo (Department of Electrical Engineering, 2022)
The main purpose of the nuclear power plant is to generate electricity and to supply it to the grid and its auxiliaries systems. Since nuclear safety overrides the production of electricity and therefore nuclear power plants are designed to protect the public and the environment from the radiation release. In order to achieve this design criteria, the nuclear safety regulations requires that the plant must have safety features incorporated in the design to remove the decay heat in a safe manner and to prevent the release of radiation to the environment. Some of the safety systems rely on constant supply of electricity to achieve their function of cooling the reactor core and to safely shutdown the plant. The total loss of Alternating Current power supply to the essential and non-essential equipment of the plant is called Station Black Out. It is critical that the system that removes decay heat in the reactor is effective to prevent the core melt. One of the design basis accidents that the nuclear power plant is design to withstand is loss of coolant accident during Station Black Out. The loss of coolant accident is more likely to occur through the primary pump seals if they do not receive adequate cooling. In this research, the seal leak rate through the primary pump was quantified using a simulator model of a Pressurised Water Reactor type, the quantified leak rates were compared to the recent Station Black Out accident that happened at a Boiling Water Reactor (Fukushima Nuclear plant Unit 1) in Japan. The simulation results of primary pump seals leakage together with the values obtained from Fukushima event were analysed and compared with primary pumps seal leakage flow rates from Westinghouse analysis. Westinghouse assumptions and analysis predicts the primary pump seal leakage during Station Black Out accident to a value of 54m³/h. The Westinghouse predictions were independently verified by Energy Technology Engineering Centre in response to Nuclear Regulation Council concerns regarding seal leakage rates on the Westinghouse Reactor Coolant Pump designs during the Station Black Out. The Energy Technology Engineering Centre calculations developed finite element structural models for all three seals to predict thermal and pressure distortion. The seal leakage of 45m³/h was determined using two-phase correlations based on Dukler constant flow slip flow model [1]. The Pressurised Water Reactor simulation performed in this research predicts a seal leakage of 39m³/h which is not far off from the studies. The radiation release due to Station Black Out was analysed and estimated using a source term code called Rascal. The amount of radiation released by a Pressurised Water Reactor plant determined to be higher than Boiling Water Reactor. The research identified the lessons drawn from the Fukushima accident. The research also highlighted the importance of effectiveness of safeguard systems that are designed to mitigate the accident during SBO.